The role of Alzheimer's disease pathology in frontotemporal dementia related syndromes. (1st February 2022) - Cordero, Indira Ruth Garcia; Snook, Emily; Multani, Namita; Taghdiri, Foad; Salvo, Cristina; Anor, Cassandra Jessica; Vasilevskaya, Anna; Varriano, Brenda Maricela; Misquitta, Karen; Tang‐Wai, David F.; Trataglia, Maria Carmela
Abstract: Background: Corticobasal syndrome (CBS) and progressive supranuclear palsy (PSP) are two syndromes associated with frontotemporal lobar degeneration (FTLD) with heterogeneous presentation and progression. Co‐pathology of FTLD and Alzheimer's disease (AD) has been described and could influence the clinical presentation of CBS and PSP. The goal of this study is to evaluate the role of AD pathology in CBS and PSP, by analyzing functional and structural neuroimaging and memory performance. Method: Patients with a clinical diagnosis of PSP and CBS ( n =15) and AD ( n =18) underwent functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI). Patients were separated according to AD biomarker positivity (CBS‐PSP‐AD, n =6) and negativity (CBS‐PSP‐noAD, n =9) based on the presence of AD biomarkers in cerebrospinal fluid. FMRI images were preprocessed to assess connectivity differences in the default mode network (DMN). DTI was analyzed to trace the bilateral superior longitudinal fasciculus (SLF) and extract its fractional anisotropy and mean diffusivity. Verbal learning and memory were assessed with the California Verbal Learning Test (CVLT‐II) and the Consortium to Establish a Registry for Alzheimer's disease (CERAD) of the Toronto Cognitive Assessment, and the z‐scores were compared between groups. Result: The DMN showed reduced functional connectivity in the groups with AD biomarker positivity (CBS‐PSP‐AD and AD patients) relative to the CBS‐PSP‐noAD group. Specifically, reduced connectivity was observed between the left angular gyrus and the left (T(23) = ‐4.02, p ‐FDR= 0.02) and right (T(23) = ‐3.48, p ‐FDR=0.04) lateral parietal regions in AD vs CBS‐PSP‐noAD. Reduced connectivity was found between the left angular gyrus, the posterior cingulate cortex (T(11) = ‐4.72, p ‐FDR=0.02) and the right hippocampus (T(11) = ‐3.94, p ‐FDR=0.04) in CBS‐PSP‐AD vs CBS‐PSP‐noAD. No differences were found in DMN connectivity in AD vs CBS‐PSP‐AD. SLF tractography metrics showed no difference between groups. Both CBS‐PSP‐AD and AD patients had significantly worse delayed memory scores than the CBS‐PSP‐noAD group (post‐hoc p ‐FDR=0.01). Conclusion: There are similarities between AD positive biomarker groups (CBS‐PSP‐AD and AD patients) in functional connectivity and memory scores, with these groups differing from the CBS‐PSP‐noAD patients. These results suggest that pathology can mediate functional connectivity patterns and influence clinical manifestation.